2018
DOI: 10.6002/ect.2016.0367
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Febuxostat, a nonpurine xanthine oxidase, is known to be effective and safe, even in patients with chronic kidney disease. However, there are insufficient data about the efficacy and safety of febuxostat in kidney transplant patients. Key words: Renal transplantation, Uric acid, Xanthine oxidase inhibitor IntroductionFebuxostat is a nonpurine xanthine oxidase inhibitor that was approved by the European Medicines Agency in 2008 and by the US Food and Drug Administration in 2009. Febuxostat is selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Bove et al showed that, in patients with renal dysfunction, the safety profile of febuxostat compared to allopurinol was better regarding relative risk (RR) of adverse events [ 80 ]. A study with kidney transplant patients showed that the use of febuxostat in those patients was safe [ 81 ]. Using febuxostat, close monitoring of patients with renal insufficiency is not required.…”
Section: Discussionmentioning
confidence: 99%
“…Bove et al showed that, in patients with renal dysfunction, the safety profile of febuxostat compared to allopurinol was better regarding relative risk (RR) of adverse events [ 80 ]. A study with kidney transplant patients showed that the use of febuxostat in those patients was safe [ 81 ]. Using febuxostat, close monitoring of patients with renal insufficiency is not required.…”
Section: Discussionmentioning
confidence: 99%